2018
DOI: 10.1088/1755-1315/105/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of emission gas and fuel consumption on SI engine fueled with low-grade bioethanol and oxygenated cycloheptanol additive

Abstract: Abstract. The use of alternative energy source is expected to reduce fossil energy consumption and exhaust emissions. One of the non-fossil energy alternatives introduced for vehicles is bioethanol, it can produce in a simple way and cheap. Low-grade bioethanol has characteristics that depend on exhaust emissions generated. Low-grade bioethanol can be used as a substitute or mixture of fuel. The mixture of bioethanol and gasoline gives an effect to the increase of octane number and reduces the emission of CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In the previous research, the distillation of low-grade bioethanol with compact distillator was experimented 6) up to the analysis of emission gas and fuel consumption on the SI engine fueled with low-grade bioethanol and oxygenated additive was discussed 13) . In this research, the authors checked further to analyze the characteristic of ethanol blend and oxygenated additive for COV IMEP and exhaust gas emissions of various fuel mixture as well as COV IMEP correlation with exhaust gas emissions at variable engine speed were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous research, the distillation of low-grade bioethanol with compact distillator was experimented 6) up to the analysis of emission gas and fuel consumption on the SI engine fueled with low-grade bioethanol and oxygenated additive was discussed 13) . In this research, the authors checked further to analyze the characteristic of ethanol blend and oxygenated additive for COV IMEP and exhaust gas emissions of various fuel mixture as well as COV IMEP correlation with exhaust gas emissions at variable engine speed were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional ethanol-gasoline blends, the introduction of additives arises concerns about their lack-of studied emission profiles and impacts on health and the environment. Studies have shown that oxygenated additives are expected to have reduced toxicity from the emissions [107]. Due to the engine fuel change, the car starting performance, dynamic performance, fuel economic performance, emissions performance, material compatibility performance, and the whole system has changed, which can be enhanced by optimizing the structure of the fuel injector to the fuel and air atomization and mixing, improve engine starting performance [108].…”
Section: Road Transport Liquid Biofuelsmentioning
confidence: 99%